The Vatican and Mussolini's Italy - Ceci, Lucia, 1967- (Religious Studies, Theology and Philosophy E-Books Online, Collection 2016, ISBN: 9789004303942., 2017)
Lucia Ceci reconstructs the relationship between the Catholic Church and Fascism. New sources from the Vatican Archives throw fresh light on individual aspects of this complex relationship: the accession of Mussolini to power, the war in Ethiopia, the racial laws, the comparison between Pius XI and Pius XII. This book offers a comprehensive reconstruction of this encounter, explaining the criteria that led Catholics to support a dictatorial, warmongering and racist regime. In contrast to the traditional periodization, the history begins with the childhood of Mussolini in the final years of the nineteenth century, and ends with the sudden collapse of his puppet regime, in 1945. This means to some extent placing in a different light the exceptional nature of the ventennio. The Italian original L'interesse superiore, Il Vaticano e l'Italia di Mussolini has won the "Friuli Storia" Prize for Studies of Contemporary History.